Comparison of the Nutritional Composition of Quinoa (Chenopodium quinoa Willd.) Inflorescences, Green Leaves, and Grains - Safiullah Pathan; Grato Ndunguru; Addissu G. Ayele (Crops, 2024)
The nutritional composition of different parts of quinoa (Chenopodium quinoa Willd.), such as sprouts, green leaves, and grains, have previously been studied in detail. This study aimed to compare the nutritional values of quinoa inflorescences against those of quinoa leaves and grains. The assessment of nutritional composition includes crude protein, crude fat, fiber, ash, carbohydrates, essential amino acids, and minerals. The proximate analysis showed that on a dry weight (DW) basis, quinoa inflorescences contain higher amounts of protein, fiber, all essential amino acids, and minerals when compared to quinoa grains. However, quinoa green leaves have higher protein and fat contents than quinoa inflorescences, while retaining all essential amino acids and minerals. Inflorescences possess a higher fiber content and a lower fat content than green leaves and grains do. In this study, nutritional assessments of inflorescences typically ranked in the middle when compared to those of green leaves and grains. These findings emphasize the nutritional potential of quinoa inflorescences as prospective ingredients to develop healthy foods and supplements that provide health benefits beyond basic nutritional functions. Nevertheless, additional research is essential to confirm and substantiate these results.